Pola Pikir Growth Mindset dalam Perspektif Nilai-nilai Islam - Mujahid, Kasori; Muharromah, Fityatul (Lembaga Yasin AlSys, 2025)
The growth mindset is the belief that abilities and intelligence can be developed through learning, perseverance, and effort. This concept is very relevant from the perspective of Islamic values, which encourage people to learn, strive, and improve themselves. In Islam, principles such as ikhtiar (effort), tawakal (surrender after effort), and sabar (patience) are in line with the growth paradigm. In addition, the Qur'an and hadith emphasize the importance of consistently improving oneself, learning from mistakes, and persisting in the face of difficulties in order to achieve spiritual and intellectual perfection. This article discusses the relationship between growth mindset and Islamic values, including its influence on Islamic education, which aims to shape people who are optimistic, confident, and oriented towards self-improvement. By incorporating the concept of growth mindset into Islamic education, it is hoped that the Muslim generation can develop into people who are optimistic, confident, and oriented towards self-improvement.